Effects of pre-exercise H2 inhalation on physical fatigue and related prefrontal cortex activation during and after high-intensity exercise - Hong, Yinglu; Dong, Gengxin; Li, Qian; Wang, Vienna; Liu, Meng; Jiang, Guole; Bao, Dapeng; Zhou, Junhong (Frontiers in Physiology, 2022)
Objective: In this study, we examined the effects of pre-exercise H2 gas inhalation on physical fatigue (PF) and prefrontal cortex (PFC) activation during high-intensity cycling exercise. Methods: Twenty-four young men completed 4 study visits. On the first two visits, the maximum workload (Wmax) of cycling exercise of each participant was determined. On each of the other two visits, participants inhaled 20 minutes of either H2 gas or placebo gas after a baseline test of maximal voluntary isometric contraction (MVIC) of thigh. Then participants performed cycling exercise under their maximum workload. Ratings of perceived exertion (RPE), heart rate (HR) and the PFC activation by using functional near-infrared spectroscopy (fNIRS) was measured throughout cycling exercise. The MVIC was measured again after the cycling. Results: It was observed that compared to control, after inhaling H2 gas, participants had significantly lower RPE at each workload phase (p < 0.032) and lower HR at 50% Wmax, 75% Wmax, and 100% Wmax during cycling exercise (p < 0.037); the PFC activation was also significantly increased at 75% and 100% Wmax (p < 0.011). Moreover, the H2-induced changes in PF were significantly associated with that in PFC activation, that is, those who had higher PFC activation had lower RPE at 75% Wmax (p = 0.010) and lower HR at 100% Wmax (p = 0.016), respectively. Conclusion: This study demonstrated that pre-exercise inhalation of H2 gas can alleviate PF, potentially by maintaining high PFC activation during high-intensity exercise in healthy young adults.